PROGRESSIVE PRACTICES OF IMPLEMENTING PUBLIC-PRIVATE PARTNERSHIP PROJECTS IN CRITICAL INFRASTRUCTURE - Zatonatskiy, Dmytro; Lieonov, Serhiy (Socio-economic relations in the digital society, 2024)
Private-public partnerships (PPPs) have become one of the leading and most effective models for investing in critical infrastructure, so the use and development of PPP models based on best practices is of particular importance in the current crisis period and during post-war recovery due to high pressure on the state budget and high risks for investment. The purpose of the study is to analyze progressive practices for the implementation of PPP projects for the critical infrastructure sectors and to develop recommendations for formulating a strategy for the usage of PPP projects in the different sectors of Ukrainian critical infrastructure. A detailed analysis of current approaches to the implementation of PPPs in the field of critical infrastructure was conducted, progressive practices of applying digitalization tools in this area were identified, and problems and prospects for their implementation were outlined. The potential factors, barriers and incentives based on regulatory, political, social, and technical factors that affect the implementation and effectiveness of PPPs in creating a modern "smart infrastructure" are highlighted. It is determined that the most important sectors for the execution of PPPs projects in most countries in recent years have been transportation, environment, education, healthcare, and telecommunications. However, the analysis of PPP projects in Ukraine concluded that the main areas of focus were the production and supply of water, gas and heat, while less attention was paid to infrastructure for education and healthcare. The article proposes strategies for the implementation of PPPs and determines the importance of each of their components for the successful implementation of PPPs, which will be relevant for Ukraine, especially at the stage of post-war reconstruction of critical infrastructure. The results of the study provide systematized information that will be useful for civil authorities, potential investors, and the scientific community.